The Reconstruction of the Border Roads and Household Welfare in Nigeria: A Gender Study - Efobi Uchenna (African Governance and Development Institute (AGDI), 2016)
This study provides an ex-ante analysis of the welfare effect from the improvement of border road infrastructure in Nigeria. It starts by describing the income distribution in the Nigerian states contained in the sample. It then analyses the relationship between income, household food expenditures, and household expenditures on imported rice. it is aimed at assessing how changes in the price of food commodities induced by border road improvements would affect different types of households. Finally, it investigates how simulated changes in local transportation costs stemming from road improvements would affect local prices of imported rice taking into consideration the simulated price changes effect on household welfare across household head gender and household area (rural and urban households). Results indicate that policies aiming to improve border roads and thereby lower transportation costs, and subsequently the price of imported rice, would be more beneficial for rural than urban households. Such policies would likely produce larger welfare gains for poorer households than richer households, and would be more beneficial for the poorest female-headed households than their male counterparts.
Keywords: D1; D6; F1; F2; R2; 330; ECOWAS; Gender; Household; Nigeria; Poverty; Trade; Welfare